Cellulitis due to shewanella algae: crucial diagnostic clues from basic microbiological tests - Ding, Chuan Hun; Abdul Wahab, Asrul; Abdul Samat Muttaqillah, Najihan; Kamarudin, Norhidayah; W.R, Saarah (Malaysian Society for Parasitology, 2019)
Shewanella spp. are infrequently implicated in human infections but they are emerging pathogens with particular significance in regions with warm climates, such as Southeast Asia. This is a case of a middle-aged diabetic and hypertensive man who presented with worsening congestive heart failure symptoms associated with fever and a painful right leg. His right leg had numerous scabs and was tender, warm and erythematous. He was provisionally diagnosed with decompensated heart failure precipitated by cellulitis and uncontrolled hypertension. His blood grew non-fermentative, oxidase-positive and motile gram-negative bacilli which produced hydrogen sulfide on triple sugar iron agar. When cultured on blood agar, mucoid and weakly β-haemolytic colonies were observed after 48 hours. API 20 NE named the isolate as Shewanella putrefaciens but 16S rRNA sequence analysis identified the organism as Shewanella algae. The patient was treated with a 10-day course of ceftazidime, which resulted in the resolution of the cellulitis.